PENGARUH LIKUIDITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2019 -2021 - Yanuariski, Wila; Wiryaningtyas, Dwi Perwitasari; Ariyantiningsih, Febri (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
This study aimed to determine the effect of Liquidity and Leverage on Company Value with Profitability as an intervening variable in Food and Beverage Sector Manufacturing Companies listed on the IDX 2019-2021. The population in this study were all Manufacturing Companies in the Food and Beverage Sector listed on the IDX in 2019-2021, which amounted to 30 companies. This research sampling technique used purposive sampling so that 12 samples were obtained, which were used for data analysis. Data analysis and hypothesis testing in this study used the Smart PLS 3.0 APPLICATION. The results of this study indicate that Liquidity and Leverage have a negative but insignificant effect on Profitability. Liquidity, and Leverage has a negative but insignificant effect on company value; Profitability has a negative but insignificant effect on the company value. Liquidity has a negative but insignificant effect on company value through Profitability. At the same time, Leverage has a positive but not significant on company value through Profitability.